Terms and conditions apply: the effect of probation length and obligation disclosure on true and false guilty pleas - Yan, Shi; Wilford, Miko M.; Ferreira, Patricia A. (Journal of experimental criminology, 2024)
Objectives Although the literature suggests wrongful guilty pleas exist, less attention has been devoted to the false guilty pleas to probation sentences. We examined the plea decision-making process when participants faced probation. Methods We conducted a 2 (guilt status: innocent or guilty) × 2 (probation length: 1 year or 5 years) × 2 (probation obligations: general or detailed disclosure) between-participant experiment using an online sample ( N = 906). Participants were randomly assigned to one of eight conditions and were asked whether they would accept a plea offer. Results Participants who were guilty and faced a shorter probation sentence were more likely to plead guilty. Participants receiving detailed disclosure were less likely to plead guilty, but the effect was less robust. Participants who faced a longer sentence and received detailed disclosure reported larger declines in plea willingness. Conclusion The findings suggest that criminal defendants are sensitive to the length and disclosure of probation sentences.